Sodium Butyrate Protects N2a Cells against Aβ Toxicity In Vitro. (15th April 2020) - Sun, Jingxuan; Yuan, Boyu; Wu, Yancheng; Gong, Yuhong; Guo, Wenjin; Fu, Shoupeng; Luan, Yongxin; Wang, Wei
Abstract : Alzheimer's disease (AD) is a common neurodegenerative disease. A β plays an important role in the pathogenesis of AD. Sodium butyrate (NaB) is a short-chain fatty acid salt that exerts neuroprotective effects such as anti-inflammatory, antioxidant, antiapoptotic, and cognitive improvement in central nervous system diseases. The aim of this study is to research the protective effects of NaB on neurons against A β toxicity and to uncover the underlying mechanisms. The results showed that 2 mM NaB had a significant improvement effect on A β -induced N2a cell injury, by increasing cell viability and reducing ROS to reduce injury. In addition, by acting on the GPR109A receptor, NaB regulates the expression of AD-related genes such as APP, NEP, and BDNF. Therefore, NaB protects N2a cells from A β -induced cell damage through activating GPR109A, which provides an innovative idea for the treatment of AD.